Impact of screening compliance on gastric cancer risk and eligibility for endoscopic treatment: a nationwide population-based cohort study - Jinju Choi; Joo Hyun Lim; Kyungdo Han; Cheol Min Shin; Byung-Ha Jeon; Ho-Kyoung Lee; Eun Hyo Jin; Seung Joo Kang (European Journal of Cancer Prevention, 2026)
To evaluate the association between compliance with the Korean national gastric cancer screening program and both gastric cancer incidence and eligibility for endoscopic treatment. Using the Korean National Health Insurance Service database, we conducted a nationwide cohort study of individuals who underwent screening endoscopy in 2012 and 2014 without prior gastric cancer. Participants were classified as high compliance, moderate compliance, or low compliance according to screening history from 2008 to 2014. Gastric cancer incidence was analyzed using Cox proportional hazards models. Among patients diagnosed with gastric cancer, endoscopic treatment ineligibility (ETI) was evaluated using logistic regression. Among 2 394 562 individuals, 26 425 developed gastric cancer during a median follow-up of 8.2 years. Screening compliance was not significantly associated with ETI among patients with gastric cancer [high compliance as reference; moderate compliance: adjusted oddsd ratio (aOR) = 1.092, 95% confidence interval (CI) = 0.994–1.200; low compliance: aOR = 0.996, 95% CI = 0.932–1.064; P for trend = 0.130] or gastric cancer incidence (moderate compliance: adjusted hazard ratio (aHR) = 1.018, 95% CI = 0.979–1.058; low compliance: aHR = 0.979, 95% CI = 0.953–1.005; P for trend = 0.079). Screening compliance was not significantly associated with ETI or gastric cancer incidence. These findings suggest that screening compliance alone may be insufficient to ensure detection at a stage amenable to endoscopic treatment and highlight the need for improved endoscopic quality and risk-stratified screening strategies.